STUDI PERBANDINGAN MEREK SEMEN (TIGA RODA, DYNAMIC, DAN MERAH PUTIH) SEBAGAI CAMPURAN PEMBUATAN BETON NORMAL TERHADAP BIAYA DAN KUAT TEKAN BETON - Indrawan, Rizski Agung; Puspitasari, Ira (Jurnal TEDC; Vol 16 No 2 (2022): JURNAL TEDC, 2022)
Concrete is a civil infrastructure material composed of hydraulic cement, coarse aggregate, fine aggregate, water and admixtures. Cement is one of the constituent materials of concrete that goes through a fabrication process and has a certain brand. This study aims to compare the compressive strength and production costs of normal concrete using three brands of cement, namely Tiga Roda cement (A), Merah Putih cement (B), and Dynamic cement (C). Concrete is made in the form of a cylinder with a size of 15 cm and a height of 30 cm, with the number of test objects 12 cylinders. This study aims to determine the comparative value of the compressive strength of the concrete produced by Portland Cement Composite (PCC) cement with cement brands A, B and C. The mix planning method uses the SNI method. From the average compressive strength value of concrete produced using cement A of 13.07 MPa and maximum compressive strength of 14.78 MPa, for concrete using B the average compressive strength of concrete produced is 14.04 MPa and maximum compressive strength 14.89 MPa, for concrete using cement C, the average compressive strength of the concrete produced is 7.77 MPa and the maximum compressive strength is 9.0 MPa.